A new promising treatment in systemic sclerosis: 5-fluorouracil. Issue 10 (October 1987) - Casas, J A; Subauste, C P; Alarcón, G S
Abstract : Twelve patients with systemic sclerosis according to American Rheumatism Association criteria were treated with intravenous 5-fluorouracil. Significant subjective and objective improvement occurred initially in the skin and subsequently in the involved viscera and vasculature. These preliminary results suggest that 5-fluorouracil may be an effective treatment for systemic sclerosis.